Interpretive contexts for traditional and current coast Tsimshian feasts - Anderson, Margaret, 1945- (Book collections on Project MUSE., 1985)
Describes the feast tradition of the Coast Tsimshian people based on fieldwork in Hartley Bay, BC. and on material from archival sources and previously published accounts. Includes a discussion of the cultural meaning of the traditional feast complex, a brief summary of feasting patterns over the last fifty years and a description of current feasts.